ANALISIS KONTEN DAN KONTEKS KEBIJAKAN PENYELENGGARAAN PEMILIHAN KEPALA DAERAH SERENTAK LANJUTAN PADA MASA PANDEMI COVID-19 DI KABUPATEN BENGKALIS - Serli Rahmaniah; Hasim As’ari (Universitas Halu Oleo, 2022)
The policy of holding simultaneous regional leader head elections continued during the Covid-19 pandemic drew a mixed response in the community, some agreed and disagreed. In response to this, the Government established PKPU Number 6 of 2020. The purpose of this research is to find out the content and context of implementation, as well as constraints in their implementation in Bengkalis Regency. Analysis with qualitative research methods, using Merillee S. Grindle's theory to find out the content of the policy and the context of its implementation. The results of research based on policy content are known that PKPU Number 6 of 2020 contains about the implementation of elections must be carried out with health protocols for prevention and control of Covid-19 with regard to the health and safety of all parties involved in organizing the election. The results of the study based on the context of implementation found that its implementation in Bengkalis Regency was in accordance with the policy content so as not to cause a new cluster of Covid-19. Policy implementation constraints are differences in conditions due to the Covid-19 pandemic, conflicts of interest between policies, constraints on budgetary resources and human resources.